Surface subsidence induced by salt cavern gas storage and its impact on railway safety: Numerical simulation and fuzzy evaluation - Jiayao Yu (Results in Engineering)
Salt cavern gas storage plays a vital role in energy security; however, its operation can induce surface subsidence, which poses a threat to nearby railway subgrades. This study focuses on the Jintan T gas storage facility. Using FLAC-3D for numerical simulation, we analyze the long-term contraction, deformation, and subsidence of the salt cavern. The results reveal that factors such as changes in cavern formation volume, the rheology of salt rock, and pressure fluctuations during gas injection and withdrawal significantly influence these processes. We propose a safety assessment framework based on the Analytic Hierarchy Process (AHP), which takes into account various factors, including cavern subsidence, train operation parameters (axle load, speed), subgrade conditions (lithology, fill characteristics), and subgrade protection measures (e.g., retaining structures and slope stabilization). A fuzzy comprehensive evaluation is subsequently performed. The findings suggest that optimizing the operating pressure of the gas storage chamber and reinforcing subgrade protection measures can enhance the safety of railway embankments. This research provides engineering guidance for improving the safety of railway infrastructure near salt cavern gas storage facilities and offers practical insights for optimizing the design and operation of underground energy storage systems.